γ-Regioselectivity of lithiated 2-buten-4-olide towards aromatic aldehydes: A simple synthesis of γ-arylidenebutenolides - Manat Pohmakotr (2018)
Lithiated 2-buten-4-olide was found to react with aromatic aldehydes regioselectively at γ-position to provide 4-(1-aryl-1-hydroxymethyl)-2- buten-4-olides which could be readily converted into the corresponding (Z)- γ-arylidenebutenolides.